Safeguarding the Lives of Children Affected by Boko Haram: Application of the SAFE Model of Child Protection to a Rights-Based Situation Analysis - Rosie O'Connor; Theresa S. Betancourt; Ngozi V. Enelamah (Harvard FXB Center for Health and Human Rights, 2020)
The Boko Haram insurgency in northeast Nigeria is responsible for the highest number of lives lost in Africa in the past decade. The country has witnessed significant violations of the United Nations Convention on the Rights of the Child, which Nigeria has signed and ratified. For instance, Nigeria had the second-highest number of children recruited to armed groups and the third-highest number of abductions in 2018. Current humanitarian efforts primarily target camps for internally displaced persons, while state strategies focus mainly on addressing security through combatant-targeted interventions. However, there is a need for more rights-based, integrated, and multifaceted approaches to tackle the interrelated threats to the security of children and their families affected by the conflict. This paper uses the SAFE model of child protection-which examines the interrelatedness of safety, access, family, and education and economic security-to analyze the challenges of children and youth affected by the conflict. We highlight the need for a gendered approach; strategies that address poverty and cultural and governance barriers; and interdisciplinary, context-specific, and autonomous child protection systems. The paper calls for urgent and increased attention to the core rights and human security needs of these children to avoid a replay of negative outcomes of conflict, where the costs and consequences propagate a cycle of violence and disadvantage.